Pancreaticopleural fistula: a rare cause of recurrent right-sided pleural effusion - Mithun Nilgiri K.; Varsha P. Rangankar; Shaily K. P.; Tushar R. Sahasrabudhe; Rishi Govind Orakkan (The Egyptian Journal of Bronchology)
Abstract Background Pancreaticopleural fistula (PPF) is an uncommon and dangerous complication of pancreatic disease and can lead to significant morbidity due to the presence of pleural effusion usually on the left side. PPF is an abnormal communication between the pancreatic duct and the pleural cavity, which occurs in patients with chronic pancreatitis or pancreatic pseudocysts. Case presentation This case report chronicles an unusual presentation of PPF in a male in his 60 s, highlighting the diagnostic challenges and the critical need for early recognition and appropriate management. The diagnosis was confirmed through a comprehensive diagnostic workup, including imaging studies and pleural fluid analysis. The patient was successfully managed with a combination of chest tube drainage, Octreotide therapy, and endoscopic intervention. Conclusion Pancreaticopleural fistula (PPF) should be considered a possible diagnosis in patients who present with an unexplained recurrent pleural effusion and have a history of pancreatic illness.